2020
DOI: 10.1007/s40675-020-00195-7
|View full text |Cite
|
Sign up to set email alerts
|

Narcolepsy Presentation in Diverse Populations: an Update

Abstract: Purpose of Review We performed a literature search to generate incidence and prevalence rates of narcolepsy in diverse populations based on current available data. Recent Findings With an onset in childhood, narcolepsy often has a delayed diagnosis due to symptoms of excessive daytime sleepiness not being recognized or being misdiagnosed. Clinical, electrophysiological, and biological tests are needed in order to diagnose narcolepsy. At the same time, the discovery of the link with the immunoregulatory human l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…There have been some studies that have not found a significant increase in the incidence of narcolepsy following H1N1 vaccination [35][36][37]. The exact cause of this increased risk is not fully understood, but it is important to note that these studies were observational and further research is needed to confirm the association between the H1N1 influenza pandemic and the incidence of narcolepsy and to understand the underlying mechanisms [38].…”
Section: Information About Narcolepsy In Different Populationsmentioning
confidence: 99%
“…There have been some studies that have not found a significant increase in the incidence of narcolepsy following H1N1 vaccination [35][36][37]. The exact cause of this increased risk is not fully understood, but it is important to note that these studies were observational and further research is needed to confirm the association between the H1N1 influenza pandemic and the incidence of narcolepsy and to understand the underlying mechanisms [38].…”
Section: Information About Narcolepsy In Different Populationsmentioning
confidence: 99%
“…Narcolepsy is a neurological disorder characterized by excessive daytime sleepiness, cataplexy (sudden loss of muscle tone during waking), and loss of boundaries between sleep and wake, with frequent state transitions and intrusions of REM sleep into the other ongoing states [ 47 , 48 , 89 , 90 ]. It is estimated that the prevalence of narcolepsy ranges from 0.2 to 600 per 100,000 people in various countries [ 91 ]. Narcolepsy is due to a deficiency of hypothalamic hypocretin/orexin [ 92 , 93 ] likely following an autoimmune etiology [ 94 ].…”
Section: Neurodevelopmental Disorders Associated With Rem Sleep Distu...mentioning
confidence: 99%
“…The various results of incidence and prevalence generated extremely high statistical heterogeneity on pooled estimates, which has been identified from a previous meta-analysis [19]. However, the sources of the heterogeneity are unclear.…”
Section: Introductionmentioning
confidence: 99%